2007
DOI: 10.3310/hta11330
|View full text |Cite
|
Sign up to set email alerts
|

The clinical effectiveness and cost-effectiveness of inhaled insulin in diabetes mellitus: a systematic review and economic evaluation

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 88 publications
0
19
0
Order By: Relevance
“…Although the effects are not widely recognised, owing to any abnormalities being slight and subclinical, in a person with CF these changes could have a greater impact. 53 This is discussed in Chapter 2.…”
Section: Lung Function In Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the effects are not widely recognised, owing to any abnormalities being slight and subclinical, in a person with CF these changes could have a greater impact. 53 This is discussed in Chapter 2.…”
Section: Lung Function In Diabetes Mellitusmentioning
confidence: 99%
“…Black et al 53 reviewed evidence on the effects of diabetes on the lung for a Health Technology Assessment (HTA) review of inhaled insulin and noted: There is a loss of lung elasticity and recoil in diabetes and a greater rate of decline in lung function with age compared with non-diabetic subjects. As a result, the lungs become stiffer and harder to inflate and deflate.…”
Section: The Effect Of Impaired Glucose Metabolism In Cystic Fibrosismentioning
confidence: 99%
“…26 A systematic review showed that Exubera was not superior to short-acting insulin in other formats and was not cost-effective, so Pfizer discontinued production. 27 MannKind Corporation (Valencia [CA], US) received US FDA approval in June 2014 for its ultrarapid-acting inhalation human insulin powder, Afrezza, which contains recombinant human insulin using the technosphere concept and is administered via MannKind's next-generation inhaler called Dreamboat. Technosphere technology is based on the pH-induced intermolecular selfassembly of a novel small-molecule excipient (fumaryl diketopiperazine).…”
Section: Insulin Inhalermentioning
confidence: 99%
“…Hurdles that must be overcome in the continued development and launch of inhaled insulin products relate specifically to the cost/benefit ratio. The annual cost of inhaled insulin is estimated to be at least 2-4 fold higher than bioequivalent amounts of subcutaneous insulin depending on the population served [59]. Prescription benefit plans will need to determine whether cost savings that arise from improved patient adherence, including prevention of chronic diabetes complications, will justify the increased cost.…”
Section: Future Of Inhaled Insulinmentioning
confidence: 99%